ROLE OF QUALITY MANAGEMENT SYSTEM (QMS) ON THE PERFORMANCE OF TEACHER IN N 2 JEMBER - Agus Dedi Mustofa; Suwignyo Widagdo; Muhaimin Dimyati (MBA - Journal of Management and Business Aplication, 2019)
This research is aimed at identifying and analyzing the roles of Quality Management System (QMS) towards the productive teachers’ performance of SMKN 2 Jember. The hypothesis of this research says Quality Management System (QMS) is partially significant effect on performance. The population of the research is productive teachers of SMKN 2 Jember. This research uses survey technique for sampling taken as a whole from the total population of productive teachers of SMKN 2 Jember. The samples of the population are 50 respondents of productive teachers of SMKN 2 Jember. The methods of data collection of this research are observation, interviews, questionnaires and documentation. The implications of research findings may contribute to the development of academic sciences and practitioners. The result of this research is to improve the productive teachers’ performance which is consistent with the concept of human resources and the aspects of the Quality Management System towards productive teachers’ performance which has partially significant effect on their performance.